Bioterrorism Preparedness Training and Assessment Exercises for Local Public Health Agencies - Dausey, David J. (RAND Corporation, 2005)
In 2003, the U.S. Department of Health and Human Services Office of the Assistant Secretary for Public Health Emergency Preparedness contracted the RAND Corporation to develop and test tabletop exercises on early local public health agency (LPHA) responses to outbreaks caused by bioterrorism. RAND developed the exercises in this manual as templates that LPHAs can customize and use to train public health workers in detecting and responding to bioterrorism events and assessing LPHAs' levels of preparedness.